1991
DOI: 10.1007/bf00383261
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cerebrovascular reserve 5 years after EC-IC bypass

Abstract: CBF-studies using the Xenon-133-inhalation technique were performed in 18 patients with a unilateral carotid artery occlusion, 5.4 years after a STA-MCA procedure. For comparison we used the CBF data of 29 patients with the same diseases who had had conservative treatment for a variable period of time. CBF was measured during rest and after the intravenous administration of 1 g acetazolamide. During rest we found a significant interhemispheric difference in both groups. After activation with acetazolamide this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Coyle et al [4] could demonstrate a delayed improvement of initially insufficient collateralization after a stroke. Holzschuh et al [6] could even demonstrate a steady decline of CBF after longer follow-up reaching the pre-operative CBF levels. Functioning of our bypasses also got worse over time with the progress of the underlying arteriosclerotic disease, suggesting a role of surgery predominantly in the first year of ischaemic events.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Coyle et al [4] could demonstrate a delayed improvement of initially insufficient collateralization after a stroke. Holzschuh et al [6] could even demonstrate a steady decline of CBF after longer follow-up reaching the pre-operative CBF levels. Functioning of our bypasses also got worse over time with the progress of the underlying arteriosclerotic disease, suggesting a role of surgery predominantly in the first year of ischaemic events.…”
Section: Discussionmentioning
confidence: 96%
“…The bypass procedure was shown to affect the vascular reserve capacity in a positive way [1,6]. Yamashita et al [17] demonstrated in 15 patients that the bypass did not increase the resting rCBF but did increase the rCRC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…18,21 Although a direct comparison with the current study is difficult due to methodological reasons, the current results indicate a beneficial effect of the bypass procedure for patients with haemodynamic impairment in terms of stroke prevention by improved cerebral haemodynamics in concordance with previous reports. 13,14,[22][23][24][25] One has to consider the racial differences in the distribution of steno-occlusive lesions, which might present with different stroke risk and also different risk-reduction by EC-IC bypass procedure. 26,27 It is noteworthy that in the international EC-IC bypass study a Japanese-Asian subgroup mainly consisting of MCA occlusive lesions showed less incidence of stroke recurrence in the surgical group though of no decisive statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…All 8 the studies in which postsurgical reactivity was reported noted a significant increase in reactivity for a combined rate of 80% (68/86). 17,19,20,[23][24][25]39 However, the original authors of the 1985 trial raised 3 objections to these case series. First, in the majority of these studies surrogate markers were used (such as blood flow and dilation response) instead of stroke and mortality rates.…”
Section: Literature Reviewmentioning
confidence: 99%